Electric Field Tuned Dipolar Interaction Between Rydberg Atoms - Jiao, Yuechun; Bai, Jingxu; Song, Rong; Bao, Shanxia; Zhao, Jianming; Jia, Suotang (Frontiers in Physics, 2022)
We demonstrate a tuned dipole interaction between Rydberg atoms by employing a controllable electric field in a cold cesium ensemble. The $|nP_{3/2}\rangle$ ($n$=38-40) Rydberg pair are prepared with a three-photon scheme and detected via the state selective field ionization technique. A weak dc electric field is used to tune Rydberg pair interaction from the van der Waals interaction regime to the dipole-dipole interaction regime. The Förster resonant interaction and an adiabatic resonance energy transfer between the $nP$ and $nS$ Rydberg states are attained by precisely tuning electric field. Rydberg excitation blockade with and without the electric field are investigated by changing the excitation pulse duration, which display that the dipole interaction induced blockade effect is stronger than the van der Waals interaction induced blockade effect. The precise control of the Rydberg interaction is of great significance to the coherent interaction in many-body systems and non-radiative collision processes.